A delegacia de homicídios de Manaus na perspectiva do Ministério Público e da Polícia Civil - Aufiero, Mário Jumbo Miranda (2008)
This paper aims to examine the police investigation, their flow and results in order to assess the delegacia of murders of Manaus in pesperctiva the public prosecutor and civilian police. The purpose of the survey will always be to provide the necessary elements to form a suspicion of crime, integrating it investigatórios the elements so that the criminal action proposal is accepted or not. However, a significant percentage of investigations police sent to prosecutors has returned to the delegacia new research or even to be attached reports which should be included in this. The assessment of the prospect of members of the public prosecutor, the Brazilian Bar Association and Civil Police investigations showed that the police investigations are returned by gaps and inconsistencies resulting from the lack of qualified personnel, physical structure, and technological expertise and adequate support from other bodies and the Medico Legal Institute and the Institute of Criminalistics that does not have sufficient resources to meet the modern requirements in the elucidation of crimes. In the absence of technical resources needed to determine evidence of guilt, many surveys are rejected.